Association of Physical Activity, Depression, Anxiety, and Stress with Menstrual Cycle Regularity among Adolescents: A Cross-Sectional Study - Sunarsih Sunarsih; Ana Mariza; Susilawati Susilawati (Poltekkes Kemenkes Palu, 2026)
Background: A regular menstrual cycle is an important indicator of adolescent reproductive health. Menstrual irregularities may reflect underlying physical and psychological problems. Evidence regarding the influence of physical activity and psychological factors on menstrual cycle regularity among adolescents remains inconsistent. This study aimed to examine the association of physical activity, depression, anxiety, and stress with menstrual cycle regularity among adolescents. Methods: A quantitative cross-sectional study was conducted among 74 female adolescents selected through purposive sampling. Inclusion criteria were post-menarche adolescents who consented to participate, while those with a history of congenital gynecological disorders were excluded. Physical activity was measured using the International Physical Activity Questionnaire–Short Form (IPAQ-SF), while depression, anxiety, and stress were assessed using the Depression Anxiety Stress Scale (DASS-42). Menstrual cycle regularity was defined as a cycle length of 21–35 days with ≤7 days variation. Data were analyzed using chi-square tests and odds ratios (OR). Results: Most respondents (71.6%) had a regular menstrual cycle. Physical activity was significantly associated with menstrual cycle regularity (p = 0.001). Depression, anxiety, and stress were also significantly associated with menstrual cycle regularity (p < 0.05), with anxiety showing the strongest association (OR = 9.444). Conclusion: Physical activity and psychological factors were significantly associated with menstrual cycle regularity among adolescents, with anxiety as the strongest factor. School-based physical activity and mental health support may help promote menstrual health. Longitudinal studies are needed to confirm causal relationships.